Isoterma de adsorção de fósforo proveniente de solução sumetida a tratamento magnético para solo argiloso - Chaves Neto, Ricardo (2019)
Phosphorus is the micronutrient and essential element most used in agriculture. A large amount of phosphorus applied to the soil is retained and unavailable to the plants due to its adsorption process. The use of magnetized treatment in agriculture has been used to increase the efficiency in water use and nutrient availability to plants. Therefore, the objective of this study was to evaluate the effects of the magnetic induction on the dynamics of phosphorus using sorption through the decantation methodology for different concentrations of phosphate solutions magnetically treated for clayey soils. Another objective was validating the phosphorus adsorption isotherm models using the Linear, Langmuir, Freundlich, and Redlich-Perteson isotherm models. We conducted the study at the Department of Water Resources and Sanitation of the Universidade Federal de Lavras (UFLA). The experiment used a design in 6x3x3 factorial scheme with six concentrations of phosphorus (0, 50, 100, 150, 200, and 300 mg/L), three incubation periods (T1 – 5 minutes; T2 – 1 hour; T3 – 24 hours), and three treatment levels (S1 – solution of distilled water and phosphorus without magnetic treatment; S2 – magnetized distilled water and phosphorus solution, and S3 – magnetized phosphate solution. We used a mono- ammonium-phosphate (MAP NH 4 H 2 PO 4 ) to elaborate the solutions, using the Sylocimol magnetizing block for magnetization. The magnetization occurred by submerging the block in the solution for 10 minutes, after which the solution was placed in a Breque of 125 mL of solution and 50 g of soil, according to Caessen (1997). The relative concentration of soluble phosphorus was obtained using an aliquot of the supernatant removed from each treatment after the incubation periods using the methodology proposed by Braga and DeFilippo (1974). Using the data obtained, we calculated the maximum adsorption capacity for each treatment, later using the simulation by isotherm models to validate and choose the model that best estimates the data. We used the Solver tool of the Excel software to adjust the models through the square sum error minimization methodology, evaluating the F test index (1 and 5%) and the coefficient of determination (R 2 ). The constants and adsorption values were submitted to the analysis of variance and Scott-Knott test at 1 and 5% of significance using the AgroStast statistical software. In conclusion, the Freundlich model presented the best adjustment for all treatments, with a coefficient of determination superior to 97% and significant at 1%. The behaviors of the adsorption curves were exponential. Therefore, one cannot use linear behavior models which presuppose a linear isotherm, as proposed by Ogata (1961), to employ simulations of phosphorus dislocation in the soil since they presuppose a linear isotherm. We obtained a positive linear behavior for the Freundlich heterogeneity constant ‘n’. Thus, the relation “1/n” decreases over time, that is, the system becomes ever more homogeneous, tending to a balance. The times of contact and concentration were the primary attributes to the adsorption for all treatments, presenting higher values of adsorption for higher times and concentrations. The order of magnetic induction was significant for all solutions, indicating the change in adsorption capacity. The solution S2 (with only magnetized water) promoted higher adsorption capacity for concentrations superior to 150 mg/L of phosphorus. Solution S3 (magnetized phosphorus solution) promoted lower adsorption values, indicating that magnetizing this treatment can promote higher phosphorus availability in the solution due to a possible crystallization of the phosphorus, the magnetic treatment did not change the adsorption capacity for the different treatments.